2003
DOI: 10.1021/bi0342261
|View full text |Cite
|
Sign up to set email alerts
|

Signal Sequence Cleavage and Plasma Membrane Targeting of the Retinal Rod NCKX1 and Cone NCKX2 Na+/Ca2+−K+Exchangers

Abstract: Retinal rod and cone photoreceptors express two distinct Na(+)/Ca(2+)-K(+) exchanger (NCKX) gene products. Both the rod NCKX1 and cone NCKX2 are polytopic membrane proteins thought to contain a putative cleavable signal peptide. A cleavable signal peptide is unusual for plasma membrane proteins; moreover, predictive algorithms suggest the presence of a cleavable signal peptide for all rod NCKX1 proteins and a noncleavable signal anchor for the cone NCKX2 proteins. In this study we have placed a peptide tag at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 19 publications
2
35
0
Order By: Relevance
“…Ref. 24) confirmed that only the small amount of mutant NCKX2 protein represented by the lower band was present in the plasma membrane (data not shown). Fig.…”
Section: Functional Analysis Of Nckx2 Mutant Proteinsmentioning
confidence: 60%
See 2 more Smart Citations
“…Ref. 24) confirmed that only the small amount of mutant NCKX2 protein represented by the lower band was present in the plasma membrane (data not shown). Fig.…”
Section: Functional Analysis Of Nckx2 Mutant Proteinsmentioning
confidence: 60%
“…This is a highly uncommon phenotype among the ϳ150 single residue NCKX2 mutants we have analyzed in the High Five cell system (also observed for the S185C and S185T mutant NCKX2 proteins in some, but not all experiments). As signal peptide cleavage appears essential for plasma membrane targeting (24), strongly reduced transport observed for the S545T NCKX2 mutant proteins may be caused by the lack of cleaved mutant NCKX2 protein present in the plasma membrane. Surface biotinylation of the S545T mutant NCKX2 protein (e.g.…”
Section: Functional Analysis Of Nckx2 Mutant Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NCKX proteins studied to date share a common predicted structure of two sets of five and six hydrophobic domains; the current topological model suggests an arrangement of five and five transmembrane segments separated by a large cytosolic loop (19). They also have a cleaved signal peptide that is essential for plasma membrane targeting, leaving a large extracellular loop at the N terminus (the C-terminal loop is also extracellular) (20). NCKX and NCX proteins share sequence homology in only two transmembrane regions forming internal repeats termed the ␣1 and ␣2 repeats.…”
mentioning
confidence: 95%
“…The various NCKX isoforms share the same overall predicted membrane topology, with 11 transmembrane segments (TMs 0-10), the first of which (TM 0) is thought to be cleaved by a signal peptidase after protein translation (20) (FIGURE 2). Glycosylation-scan- 19).…”
Section: Structure and Functionmentioning
confidence: 99%